2017
DOI: 10.14309/00000434-201710001-00816
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Complication of ERCP: Duodenal Perforation Due to Biliary Stent Migration

Abstract: Placement of pancreatobiliary stents during endoscopic retrograde cholangiopancreatography (ERCP) is a common practice. Stents can be used for management of various entities, including malignant biliary strictures, large obstructing bile duct or pancreatic duct stone burden, benign biliary or pancreatic duct strictures, bile leak, papillary stenosis, pseudocyst drainage, and prevention of post-ERCP pancreatitis. Migration of a biliary stent is a known potential complication of ERCP, with distal migration occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Similar cases were reported in a retrospective observational study by Gromski et al, where in six cases of duodenal perforation involving biliary stents were reported after endoscopic retrograde cholangiopancreatography for both benign and malignant cases [7] . The mean age was 65.2 years, 4 of the procedures were performed for malignant biliary obstruction, and plastic biliary stents were used in 6 cases.…”
Section: Discussionsupporting
confidence: 84%
“…Similar cases were reported in a retrospective observational study by Gromski et al, where in six cases of duodenal perforation involving biliary stents were reported after endoscopic retrograde cholangiopancreatography for both benign and malignant cases [7] . The mean age was 65.2 years, 4 of the procedures were performed for malignant biliary obstruction, and plastic biliary stents were used in 6 cases.…”
Section: Discussionsupporting
confidence: 84%
“…As shown in Table 1, 13 cases, including our case, of endoscopic closure using an OTSC for gastrointestinal perforation due to bile duct stent migration have been reported thus far [6,[12][13][14][15]. Endoscopic closure was successful in all 13 cases, and OTSC closure was considered safer than clip closure.…”
Section: Discussionmentioning
confidence: 62%
“…However, gastrointestinal penetration or transmural perforation due to stent migration is rare, with an incidence of < 1% [4]. Perforation due to displacement of the biliary stent can occur mainly in the duodenum and in other parts of the small intestine and the colon [5][6][7][8][9]. In recent years, endoscopic closure of gastrointestinal perforations using an over-the-scope clip (OTSC) has been shown to be effective with a high success rate [6,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation